Analysis of Maternal and Child Nutrition Trends: Provision of Iron Supplements and the Incidence of Low Birth Weight (LBW) in Donggala Regency, Central Sulawesi Province, 2020–2023 - Angel Latif; Ainani (Journal of Health Science and Pharmacy, 2025)
Background: Maternal nutrition plays a pivotal role in determining neonatal health outcomes. Inadequate iron intake and poor adherence to iron supplementation increase the risk of maternal anemia and the incidence of low birth weight (LBW). This issue is particularly concerning in Donggala Regency, Central Sulawesi, where recent years have seen a decline in iron supplementation coverage alongside an increase in LBW prevalence. Objective: This study aims to analyze the trends in iron supplementation coverage among pregnant women and the incidence of LBW in Donggala Regency from 2020 to 2023. Methods: A descriptive quantitative approach was employed using secondary data obtained from the Central Sulawesi Provincial Health Profile. Trend analyses were conducted using graphical representations to compare changes in iron supplementation coverage and LBW incidence. Results: Iron supplementation coverage declined from 84% in 2020 to 75% in 2023, while LBW incidence increased from 2.2% in 2020 to 6.1% in 2023. The inverse relationship between supplementation coverage and LBW incidence suggests a potential association between reduced iron supplementation and impaired fetal growth. Conclusion: The declining coverage of iron supplementation and the rising incidence of LBW highlight the urgent need for strengthened nutrition education, enhanced antenatal monitoring, and improved access to maternal healthcare services. These findings can inform targeted interventions and policy development to improve maternal and neonatal health outcomes in the region. Keywords: maternal nutrition, iron supplementation, low birth weight, health trends, Indonesia